ANALISIS FINANSIAL USAHA PEMBESARAN IKAN LELE POKDAKAN SUMBER REJEKI KABUPATEN KEDIRI - Saputra, Leny Bima; Widodo, Moch. Wahyu; Meilina, Restin (Universitas Prof. Dr. Hazairin SH, 2022)
Sumber Rejeki Fish Cultivation Group or usually called POKDAKAN Sumber Rejeki is agroup of farmers who’s cultivating fish especially catfish in Bangkok Village, Gurah District,Kediri Regency. This group was founded in 2017 and has a purpose to embrace the villagecommunity to work together in advancing the catfish farming business owned by its members.The purpose of this study was to analyze the feasibility of cultivating catfish (Clarias sp) atPOKDAKAN Sumber Rejeki which is analized by Revenue on Costs Ratio (R/C Ratio), BreakEvent Point (BEP), and Payback Period (PP), and Switching Value. The population of thisstudy were all catfish cultivators in POKDAKAN Sumber Rejeki Bangkok village with asample of 30 respondents. The analysis technique used is Revenue on Costs Ratio (R/CRatio), Break Event Point (BEP), and Payback Period (PP), and Switching Value. Based onthe results of financial analysis using the method of calculating the R/C Ratio with anaverage value of 1.09, price BEP of Rp 13,786, volume BEP of 3818 kg, PP an average valueof 1.14. While the results of the price sensitivity analysis some members suffered losses.Broadly speaking, the POKDAKAN Sumber Rejeki catfish enlargement business is in afinancially viable, profitable, and fast return on investment condition.